2009
DOI: 10.1021/jp903470n
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Structure and Thermodynamics of Carrier-Assisted Uranyl Ion Extraction

Abstract: We present molecular dynamics simulations of interfaces relevant to the selective chemical extraction of uranyl ions from aqueous solution. These molecular-level simulations model ion transfer in the PUREX process and in synthetic, selective membranes. We first present simulations of water/oil interfaces modified by incorporation of tributyl phosphate (TBP) into the oil phase (hexane). A range of concentrations is examined, from a single TBP molecule to values close to those utilized in the PUREX process. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 55 publications
4
44
0
Order By: Relevance
“…And considering that the selective extraction of uranium from the aqueous system is now a very active branch of the field of metal ion separations, the proposed reaction mechanism can be extended to not only LLE for the separation of uranium(VI), but also for the extraction of other aqueous metal cations based on both SPE and LLE approaches, involving metal-ligand interaction. And moreover, similar to the case of the nitrogen atom in the urea ligand which endows the ketone oxygen atom in the same ligand with more negative charge and stronger bonding ability to uranyl, our DFT calculations suggest that other soft atoms, such as phosphorus [36][37][38][39][40][41]58 and sulfur, 59,63 will also enhance the affinity of the coordinating oxygen for uranium when they appear at the appropriate location.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…And considering that the selective extraction of uranium from the aqueous system is now a very active branch of the field of metal ion separations, the proposed reaction mechanism can be extended to not only LLE for the separation of uranium(VI), but also for the extraction of other aqueous metal cations based on both SPE and LLE approaches, involving metal-ligand interaction. And moreover, similar to the case of the nitrogen atom in the urea ligand which endows the ketone oxygen atom in the same ligand with more negative charge and stronger bonding ability to uranyl, our DFT calculations suggest that other soft atoms, such as phosphorus [36][37][38][39][40][41]58 and sulfur, 59,63 will also enhance the affinity of the coordinating oxygen for uranium when they appear at the appropriate location.…”
Section: Discussionsupporting
confidence: 64%
“…The charge transfer can be evaluated by the secondorder interaction energy between donor and acceptor orbitals, E (2) , for n(N)p* (CQO) which are listed in Table 2. In addition, further DFT calculations found out that other soft atoms, such as phosphorus [36][37][38][39][40][41]58 and sulfur, 59 will also enhance the bonding ability of the directly coordinated oxygen atom when they appear at appropriate locations (see ESI 4 †).…”
Section: The Role Of Nitrogen Atoms In the Urea Ligandmentioning
confidence: 99%
“…From a mechanistic point of view, based on the MD simulations, we proposed that the complex forms at nanoscopic interfaces between water and oil. These features have been supported by more recent studies: firstly, by a potential of mean force (PMF) simulation (similar to the PTI technique used in conjunction with CPMD) of interface crossing by TBP, [UO 2 (NO 3 ) 2 ] and the [UO 2 (NO 3 ) 2 (TBP) 2 ] complex at the water/ TBP + hexane interface, [57] and secondly by an MD study on UO 2 2 + NO 3 À (plus added H 3 O + ions) at the water/dodecane + TBP interface. [58] Other MD simulations at liquid/liquid interfaces involve (UO 2 (NO 3 ) 2 (CMPO) n complexes with bidentate CMPO ligands (Scheme 1).…”
Section: Scheme 1 Ionic Constituents Bmimentioning
confidence: 79%
“…Some molecular dynamics simulation studies h ave suggested that many t y pes of u ranyl-TBP complexes, such as UO 2 (NO 3 ) 2 (TBP) 2 , UO 2 (NO 3 ) 2 (H 2 O)(TBP) 2 , and UO 2 (NO 3 ) (TBP) 4 , are formed at the interface before extraction into the organic phase. [15][16][17][18] However, there have not been any experimental evidence of the complex formation at the interface. Figure 4 shows the vibrational spectra of the air/aqueous-TBP interface, and the bands observed are due to the P=O stretch of TBP, 9 indicating the existence of TBP at the interface.…”
Section: Resultsmentioning
confidence: 99%